Trust, Racial Fragmentation and Income Inequality: New Evidence from the U.S. - Andrea Tesei (Center for Economic Studies and ifo Institute (CESifo), 2014)
Existing studies of trust formation in U.S. metropolitan areas have found that trust is lower when there is more income inequality and greater racial fragmentation. I add to this literature by examining the role of income inequality between racial groups (racial income inequality). I find that greater racial income inequality reduces trust. Also, racial fragmentation is no longer a significant determinant of trust once racial income inequality is accounted for. This result is consistent with a simple conceptual framework where concurrent differences in race and income are especially detrimental for trust formation. I find empirical support for further implications deriving from this assumption. In particular, I show that racial income inequality has a more detrimental effect in more racially fragmented communities and that trust falls more in minority groups than in the majority group when racial income inequality increases.
Keywords: H73; I31; J15; 330